Temporal Evolution of Marine Sediments Pollution in Dakar: Polycyclic Aromatic Hydrocarbons Determination by Gas Chromatography-Mass Spectrometry - Ndiaye, Momar; Diop, Abdoulaye; Gago Martínez, Ana; Antonio Rodríguez Vázquez, José (Asian Journal of Chemistry, 2013)
Marine sediments selected from the region of Dakar, Senegal and collected between year 2004 and 2008 were studied for their content on polycyclic aromatic hydrocarbons which were determined by GC-MS. The sampling sites (Port of Dakar, Hann, Soumbédioune and Mbao) were chosen according to the various commercial activities or particular situation of the given area. Thus, Dakar port is where the big tanks for storing and supplying the refined fuels to the different petrol stations around the city, ships, etc. are placed. Hann and Soumbédioune are the sites where urban wastewaters flow throughout the East and West canals, while Mbao is the place where the African Oil Refinery is located. A short-timed accumulation of pollutants within the sediments selected by polycyclic aromatic hydrocarbon was also noticed with their concentrations increasing from year 2004 to 2008 samples. The results show that the harbor zone has the highest level, which is followed by the sites of Soumbédioune, Mbao and Hann. These studies are an inventory of fixtures need to be carried on to provide basic scientific data to political decision makers in order to look for resolving the solution.